A bifunctional oleate 12‐hydroxylase: desaturase from Lesquerella fendleri - Pierre Broun; Sekhar Boddupalli; Chris Somerville (1998)
Summary LFAH12 , an oleate 12‐hydroxylase gene from Lesquerella fendleri (L.) was isolated on the basis of nucleotide sequence similarity to an oleate hydroxylase gene from Ricinus communis (L.). Transgenic Arabidopsis plants containing the Lesquerella gene under transcriptional control of the cauliflower mosaic virus 35S promoter accumulated ricinoleic, lesquerolic and densipolic acids in seeds, but not in leaves or roots. However, hydroxylase activity was detectable in crude extracts of vegetative tissues. The discrepancy between the presence of activity and the lack of hydroxy fatty acids suggests selective removal and breakdown of hydroxy fatty acids in vegetative organs. High levels of LFAH12 mRNA accumulation did not lead to correspondingly high levels of protein accumulation, suggesting that accumulation of the hydroxylase may be controlled post‐transcriptionally. Expression of the L. fendleri gene in transgenic plants of a fad2 mutant of Arabidopsis , which is deficient in cytoplasmic oleate Δ12 desaturase activity, resulted in partial suppression of the mutant phenotype in roots. Thus, unlike the hydroxylase from R. communis , the L. fendleri enzyme has both hydroxylase and desaturase activities. Fusion of the 5′ flanking region of the LFAH12 gene to the β‐glucuronidase coding sequence resulted in a high level of early seed‐specific expression of β‐glucuronidase activity in transgenic Arabidopsis plants.